Use of saline waste water from demineralization of cheese whey for cultivation of Schizochytrium limacinum PA-968 and Japonochytrium marinum AN-4 - Humhal, Tomas; Kastanek, Petr; Jezkova, Zuzana; Cadkova, Anna; Kohoutkova, Jana; Branyik, Tomas (Bioprocess and biosystems engineering, 2017)
Saline waste water from demineralization of cheese whey was used as the main component of waste saline medium (WSM) for cultivation of thraustochytrids. The suitability of WSM for cultivation of Schizochytrium limacinum PA-968 and Japonochytrium marinum AN-4 was evaluated by comparison with cultivation on nutrient medium (NM) in shake flask and fermenter cultures. Biomass productivities achieved in WSM for the thraustochytrids were comparable with those in NM for both shake flask and fermenter cultures. The maximum total lipid content (56.71% dry cell weight) and docosahexaenoic acid productivity (0.86 g/L/day) were achieved by J. marinum AN-4 grown on WSM in shake flask and fermenter cultures, respectively. A cost estimate of WSM suggests that this medium could result in lower production costs for thraustochytrid biomass and lipids and contribute to the effective reduction in saline diary process waste water.
Keywords: Heterokontophyta; Waste Water; soli; Nitrogen; lipidy; kyseliny dokosahexaenové; odpadní voda; potravinářská mikrobiologie; Whey Proteins; Docosahexaenoic Acids; Food Microbiology; dusík; Dairying; Fatty Acids; Schizochytrium limacinum; Shake flask; Bioreactors; Cheese; průmyslová mikrobiologie; syrovátkové proteiny; Lipids; Japonochytrium marinum; Saline waste water; sýr; mlékárenství; Wastewater; Salts; Whey; Industrial Microbiology; fermentace; Docosahexaenoic acid; Fermentation; mastné kyseliny; Bioreactor; bioreaktory; elektrody; syrovátka; Biomass; Stramenopiles; Electrodes; biomasa